2016
DOI: 10.1007/s13198-016-0444-0
|View full text |Cite
|
Sign up to set email alerts
|

Generalized fuzzy cognitive maps: a new extension of fuzzy cognitive maps

Abstract: A fuzzy cognitive maps (FCM) is a cognitive map within the relations between the elements. FCM has been widely used in many applications such as experts system and knowledge engineering. However, classical FCM is inherently short of sufficient capability of representing and aggregating uncertain information. In this paper, generalized FCM (GFCM) is proposed based on genetic algorithm and interval numbers. An application frame of GFCM is detailed. At last, a numerical example about socioeconomic system is used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…Mago et al (2014), for example, tested k = {0.8, 0.7, 0.6, 0.5, 0.45, 0.4, 0.3} and concluded that their system outputs were more accurate for k = 0.7. Kang et al (2016) also state that values of k equal to or close to 1 are ideal, since they provide the possibility of differentiation between the results after convergence, providing better interpretability.…”
Section: Grey Systems Theorymentioning
confidence: 99%
“…Mago et al (2014), for example, tested k = {0.8, 0.7, 0.6, 0.5, 0.45, 0.4, 0.3} and concluded that their system outputs were more accurate for k = 0.7. Kang et al (2016) also state that values of k equal to or close to 1 are ideal, since they provide the possibility of differentiation between the results after convergence, providing better interpretability.…”
Section: Grey Systems Theorymentioning
confidence: 99%
“…In the proposed approach, after determining critical risk factors by fault tree analysis, they modeled the system by the FCM relative degree analysis, and the overall safety level was calculated using a fuzzy comprehensive evaluation. Kang et al [67,68] evaluated oil-spill emergency response capability to reduce pollution and accidents. Their proposed approach includes FCM to model the system and calculate weights in the first level, analytic hierarchy process to find the weights in the second level of the distribution model, and fuzzy comprehensive evaluation to measure oil-spill emergency response capability level.…”
Section: Modelingmentioning
confidence: 99%
“…In this equation, the lambda value corresponds to a constant defined by the system designer. Kang et al (2016) state that values of λ equal to or close to 1 are ideal, since they provide the possibility of differentiation between the results after convergence of the system, providing better interpretability. In summary, the system activation consists in iteratively multiplying the initial state vector and the relationship matrix within the chosen activation function, used to monotonically map these values evolution.…”
Section: Fuzzy Cognitive Mapsmentioning
confidence: 99%